A hypersensitive response-like reaction is involved in hybrid weakness in F1 plants of the cross Capsicum annuum × Capsicum chinense - Shiragaki, Kumpei (Breeding science, 2020)
Copyright © 2020 by JAPANESE SOCIETY OF BREEDING.